An investigation of organic mixed coolant (Palm Olein) for green machining. Issue 2 (4th March 2014) - Lee, T.S.; How, C.F.; Lin, Y.J.; Ting, T.O.
Abstract : Purpose: – The purpose of this paper is to investigate and contribute to a better understanding of cutting process characteristics using the proposed RBD Palm Olein-based organic mixed coolant. Design/methodology/approach: – In this research, refined, bleached and deodorized (RBD) Palm Olein is selected as the base oil for organic coolant and mixed coolant (base oil mixed with chemicals) to compare with the cutting performance of industrial water-soluble chemical (inorganic) coolant. Using coated carbide tool, JIS SS400 Mild Steel was tested in milling process. At fixed spindle speed, the relations between feed rate and depth of cut (DOC) on cutting temperature and surface roughness were investigated. Also, the dynamic viscosity, specific heat capacity and pH level for each coolant are taken into consideration. Findings: – As predicted, cutting fluid with lower viscosity removes more heat. The cutting temperature increased with increasing feed rate and DOC. However, surface roughness increased with increasing feed rate but decreased with increasing DOC. From the data gathered, the proposed RBD Palm Olein-based organic mixed coolant showed better heat removal properties than organic coolant and it produced a far better machined surface than inorganic coolant. Originality/value: – Overall, the proposed organic mixed coolant has shown great potential to be a good cutting fluid when balance between cooling properties and lubricity, and consistent quality of cutting fluids are sought to produce environmental friendly quality workpiece.